Increase in VEGF secretion from human fibroblast cells by bioactive glass S53P4 to stimulate angiogenesis in bone. Issue 11 (17th January 2014) - Detsch, Rainer; Stoor, Patricia; Grünewald, Alina; Roether, Judith A.; Lindfors, Nina C.; Boccaccini, Aldo R.
Abstract Bioactive glasses (BAGs) are being investigated for the repair and reconstruction of bone defects, as they exhibit osteoconductive and osteostimulatory potential. However, successful bone regeneration requires also the neovascularization of the construct which is, among other factors, guided by vascular endothelial growth factor (VEGF). In this study, BAG S53P4 (53% SiO2, 23% Na2O, 20% CaO, 4% P2O5) is investigated in relation to VEGF‐release and response of fibroblast cells. Human CD‐18CO fibroblasts were cultivated in contact with different granules of different sizes (0.5–0.8 mm, 1.0–2.0 mm, and 2.0–3.15 mm) and at different concentrations (0–1 wt/vol % of BAG) for 72 h. The analysis of morphology revealed no toxic effect for all granule sizes and concentrations. Compared with the reference, lactate dehydrogenase‐activity of CCD‐18CO cells increased in contact with BAG samples. The VEGF release from CCD‐18CO fibroblasts cultured on different granule sizes and at different concentrations after 72 h of incubation was quantified. It was found that particles of 0.5–0.8 mm and 1.0–2.0 mm in size enhanced VEGF release, whereas BAG particle sizes of 2.0–3.15 mm led to inhibition of VEGF release. The results are relevant to understand the influence of the particle size and concentration of BAG S53P4 on VEGF expression and neovascularization. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4055–4061, 2014.